2021
DOI: 10.3390/app11104629
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Decontamination Induced by Light and Not by Heat: Comparison between Oxygen High Level Laser Therapy (OHLLT) and LANAP

Abstract: In periodontology, lasers have been suggested for the nonsurgical treatment of chronic periodontitis. Many wavelengths were tested, but unfortunately, most parts were not efficient. An Nd:YAG laser was applied in a specific protocol named the laser-assisted new attachment procedure (LANAP). LANAP seems to facilitate the refurbishment of new tissues from supporting structures of the periodontium, wherein the unhealthy surface of the roots exhibits pristine attachments in human beings. Photodynamic therapy (PDT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…The literature reported that subgingival debridement (scaling and root planning) leads to a temporary change in the composition of subgingival microorganisms, including species like the microflora found in healthy periodontal sites [56,57]. However, recolonization of the periodontal sites by spirochetes and motile rods one to two months after the end of the therapy, together with the persistence of red and orange complexes bacteria in the deepest part of the periodontal pockets, make it clear that non-surgical periodontal treatment (SRP) is not sufficient in contrasting chronic periodontitis [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…The literature reported that subgingival debridement (scaling and root planning) leads to a temporary change in the composition of subgingival microorganisms, including species like the microflora found in healthy periodontal sites [56,57]. However, recolonization of the periodontal sites by spirochetes and motile rods one to two months after the end of the therapy, together with the persistence of red and orange complexes bacteria in the deepest part of the periodontal pockets, make it clear that non-surgical periodontal treatment (SRP) is not sufficient in contrasting chronic periodontitis [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…First of all, we observed that in the literature there were studies that analyzed the effectiveness of laser photobiomodulation in orthodontics during the positioning of elastic separators [25,26] or orthodontic archwires and evaluate their analgesic efficacy according to the protocols [27,28]. There were several works on the efficacy of lasers and LEDs, not only in orthodontics but even in other fields of dentistry, especially in the management of periodontitis and perimplantitis [29][30][31][32][33][34][35]. However, no study has ever involved the analgesic efficacy of the laser in palatal expansion [36].…”
Section: Discussionmentioning
confidence: 99%
“…Diode lasers are increasingly being used as part of the laser assisted new attachment procedures (LANAP), whereby the epithelium lining the pocket is removed in an attempt to gain new attachment. 47 To perform this procedure, after the completion of scaling and root planing the optical fiber is introduced into the periodontal pocket and ascending and descending movement are performed. Through the duration of the procedure the optical fiber must be maintained parallel to the tooth root main axis, with the laser being rotated around the perimeter of each involved tooth.…”
Section: Removal Of Periodontal Pocket Liningmentioning
confidence: 99%